Hydraulic characteristics of the groundwater aquifer in Al-Dhibaei Area South Tikrit - Saad Maulood Saab; Sabbar Abdullah Salih; Raad Hoobi Rzoqi (Tikrit Journal of Pure Science, 2023)
In this study the ground water recharge was estimated, with studying the hydrological conditions Al-Dhubaei region which located 5 km to the southwest of Tikrit city. Depending on the data of Tikrit meteorological station, the averages monthly climatic elements (rainfall, temperature and evaporation) were studied for a period of (1989-2013), the average annual rainfall reached 166.72 mm, as well as the evaporation-transpiration rates were calculated using Thornthwait method. The water balance of the area was calculated and the results show that the ratio of water surplus were reached to 38.87% of the total annual rainfall, and the groundwater recharge equal to 4.66×106 m3/year.